2021
DOI: 10.3389/fpls.2021.756795
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Phytochrome-Interacting Factors Enhances Photoresponses of Seedlings and Delays Flowering With Increased Plant Height in Brachypodium distachyon

Abstract: Phytochromes are red and far-red photoreceptors that regulate plant growth and development under ambient light conditions. During phytochrome-mediated photomorphogenesis, phytochrome-interacting factors (PIFs) are the most important signaling partners that regulate the expression of light-responsive genes. However, the function of PIFs in monocots has not been studied well. In this study, using RNA interference (RNAi), we investigated the functions of BdPIL1 and BdPIL3, two PIF-like genes identified in Brachyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…In Petunia and other crops, B promoted elongation and reduced the number of lateral branches and biomass allocation of lateral branches (Miao et al, 2019). Under B treatment, phytochrome had no activity, resulting in internode elongation (Hoang et al, 2021) and plant height increase, which was inconsistent with the findings of our study. Our results showed that the plant height and internode length were significantly shortened under the B treatment, in contrast with the R treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…In Petunia and other crops, B promoted elongation and reduced the number of lateral branches and biomass allocation of lateral branches (Miao et al, 2019). Under B treatment, phytochrome had no activity, resulting in internode elongation (Hoang et al, 2021) and plant height increase, which was inconsistent with the findings of our study. Our results showed that the plant height and internode length were significantly shortened under the B treatment, in contrast with the R treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Plant height and leaf area of transgenic soybean are decreased by overexpressing PIF4 ( Arya, Singh & Bhalla, 2021 ). The deletion of PIF1 and PIF3 results in an increase in plant height, longer internodes, and late flowering ( Hoang et al, 2021 ). The light-harvesting complex II (LHC II) functions as a light receptor and is related to the absorption of light ( Gu et al, 2017 ; Sen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to phyB, phyA interacts with PIF3, aiding in PIF3 degradation and positively regulating seedling de-yellowing. While phyA's role in Arabidopsis flowering regulation via PIF3 remains unreported, its interaction with BdPIL1/BdPIL3 in Brachypodium distachyon suggests a physiological function in promoting inflorescence induction (Ni et al, 1998;Kim et al, 2003;Hoang et al, 2021).…”
Section: Regulation Of Plant Flowering Time By Phyamentioning
confidence: 99%